A high temperature resistant flame retardant PP corrugated pipe and preparation method thereof

By using maleic anhydride grafted rubber elastomer copolymer in polypropylene corrugated pipes with flame retardant, antioxidant and anti-copper agents, the flammability and degradation of polypropylene corrugated pipes in high temperature environments is solved, and a corrugated pipe with high temperature resistance and long life is achieved.

CN119752026APending Publication Date: 2025-04-04SHENZHEN JDD TECH NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882608.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Polypropylene corrugated pipes are flammable in high temperature environments, have insufficient flame retardant properties, and their sensitivity to copper ions leads to accelerated degradation and aging, affecting service life.

Method used

High temperature-resistant flame-retardant PP corrugated pipe is prepared by using a combination of maleic anhydride grafted rubber elastomer copolymer with flame retardant, antioxidant and anti-copper agents.

Benefits of technology

It achieves high flame retardant properties of polypropylene corrugated pipes (to UL 94-V0 grade), excellent high-temperature aging performance and excellent copper damage resistance, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198561400000242
    Figure BDA0005198561400000242
  • Figure BDA0005198561400000251
    Figure BDA0005198561400000251
  • Figure BDA0005198561400000263
    Figure BDA0005198561400000263
Patent Text Reader

Abstract

The present invention belongs to the technical field of polypropylene, and particularly relates to a high temperature resistant flame retardant PP corrugated pipe and a preparation method thereof. A high temperature resistant flame retardant PP corrugated pipe, the raw materials of which are measured by weight, include: 40-60 parts of PP resin, 3-10 parts of rubber elastomer, 5-10 parts of maleic anhydride grafted rubber elastomer copolymer, 0.6-0.8 parts of maleic anhydride, 18-22 parts of flame retardant, 0.3-1 parts of first composite antioxidant, 0.5-1 parts of second composite antioxidant and 0.5-1.2 parts of lubricant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polypropylene, and in particular relates to a high-temperature-resistant and flame-retardant PP corrugated pipe and a preparation method thereof. Background Art

[0002] Polypropylene corrugated tube is a corrugated tube made of polypropylene as the main material. Due to its excellent performance, it is widely used in wiring harness protection in many fields such as automobiles, electronics, and machinery. As a semi-crystalline plastic material, polypropylene corrugated tube not only has excellent thermal stability and chemical corrosion resistance, but also can maintain its structural integrity and protection function in various complex environments. Therefore, it has become an important choice for wire harness protection covers and is widely used in automotive wire harness protection, wire and cable coating, and wire harness protection for household appliances and precision machine tools. However, the inherent defects of polypropylene itself limit its wider application, especially in terms of flame retardancy and high temperature aging performance, which has become a technical problem that needs to be solved urgently in the industry.

[0003] First of all, polypropylene is a flammable material with an oxygen index of only about 18%, which makes it difficult to meet high flame retardant requirements such as UL 94-V0 grade. This problem is particularly prominent in corrugated pipe applications because wire harness protection materials are usually directly exposed to potential high temperature or fire source environments, such as complex heat loads in the engine compartment of a car or local overheating that may occur during long-term operation of electrical equipment. In order to meet the flame retardant requirements, the industry generally uses brominated flame retardants to modify polypropylene. The introduction of brominated flame retardants can significantly improve the flame retardancy of the material and inhibit the spread of flames by releasing bromine free radicals during the combustion process. However, although this modification method improves the flame retardant properties of polypropylene in the short term, it inevitably brings about the deterioration of high temperature aging performance. Under high temperature conditions, brominated flame retardants are easily decomposed to produce acidic bromine free radicals. These free radicals are highly active and will attack the chemical bonds in the polypropylene molecular chain, especially the tertiary hydrogen on the chain, resulting in rapid degradation of polypropylene. This degradation phenomenon will not only reduce the mechanical properties of the corrugated pipe, but may also cause problems such as surface powdering and brittle cracking, seriously affecting its service life.

[0004] In addition, polypropylene bellows will inevitably come into contact with copper parts in many applications, and polypropylene materials are extremely sensitive to copper ions. In the presence of copper ions, the degradation and aging rate of polypropylene will be significantly accelerated. This phenomenon is usually called "copper damage". Copper ions play a catalytic role in the degradation process of polypropylene, accelerating the oxidative degradation reaction. In order to inhibit copper damage, anti-copper damage agents are usually added to the formula. However, traditional anti-copper damage agents are prone to precipitation during long-term use at high temperatures, resulting in surface stickiness, which not only affects the appearance of the product, but may also lead to a decrease in actual performance. Therefore, how to improve the flame retardant properties of polypropylene corrugated pipes while overcoming the adverse effects of brominated flame retardants on high-temperature aging, as well as solving the stability problem of anti-copper damage agents, has become a core technical problem in the industry.

[0005] In the current technical solutions, for example, the flame retardant or anti-copper damage agent is fixed to the polypropylene matrix through grafting technology. Although it alleviates the contradiction between flame retardancy and aging resistance to a certain extent, the preparation process is complicated, the cost is high, and it is difficult to meet the comprehensive requirements of flame retardancy, high-temperature aging performance and anti-copper damage performance at the same time. In addition, some patented technologies replace brominated flame retardants with halogen-free flame retardants. Although they have advantages in environmental protection and safety, their flame retardant efficiency is usually low, and it is difficult to meet the high requirements of bellows for flexibility and mechanical properties. Therefore, how to prepare a polypropylene corrugated pipe with high flame retardancy (reaching UL 94-V0 grade), excellent high-temperature aging performance (long-term use above 150°C), and excellent anti-copper damage performance (still highly stable when in contact with copper) through material formula design and process optimization is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the above-mentioned shortcomings and provide a high temperature-resistant and flame-retardant PP corrugated pipe and a preparation method thereof.

[0007] A high temperature resistant flame retardant PP corrugated pipe, the raw materials of which are measured by weight: 40-60 parts of PP resin, 3-10 parts of rubber elastomer, 5-10 parts of maleic anhydride grafted rubber elastomer copolymer, 0.6-0.8 parts of maleic anhydride, 18-22 parts of flame retardant, 0.3-1 parts of first composite antioxidant, 0.5-1 parts of second composite antioxidant and 0.5-1.2 parts of lubricant.

[0008] Furthermore, the raw materials, by weight, also include 6 to 12 parts of flame retardant synergist, 0.5 to 3 parts of copper resistant agent, 0.3 to 1 part of halogen absorber, 0.2 to 0.5 parts of nano inorganic filler and 1 to 1.5 parts of masterbatch.

[0009] Furthermore, the PP resin includes one or two of homopolymer PP and copolymer PP; the copolymer PP brand includes one or more of K8303, K7002, TF1007, K8003, F5005A, and B4902;

[0010] The rubber elastic body includes one or more of EPDM rubber, polyolefin elastomer, EPDM rubber, butadiene rubber, natural rubber, and styrene-butadiene-styrene copolymer;

[0011] The flame retardant includes one or more of tris(tribromoneopentyl)phosphate, tris(2,3-dibromopropyl)isocyanurate, brominated epoxy resin, decabromodiphenylethane, octabromoether, tetrabromobisphenol A, hexabromocyclododecane, and brominated polystyrene;

[0012] The first composite antioxidant includes a first main antioxidant and a first auxiliary antioxidant, wherein the first main antioxidant includes one or more of antioxidant 1010, antioxidant CA, antioxidant 2246, and antioxidant 1024; the first auxiliary antioxidant includes one or more of antioxidant DLTDP, antioxidant DSTDP, antioxidant 412S, and antioxidant SE-10;

[0013] The second composite antioxidant includes a second main antioxidant and a second auxiliary antioxidant, wherein the second main antioxidant includes one or more of antioxidant 1076, antioxidant 264, antioxidant 245, antioxidant 3114, and antioxidant 1098; the second auxiliary antioxidant includes one or more of antioxidant 168, antioxidant 626, and antioxidant P-EPQ;

[0014] The lubricant includes one or more of paraffin wax, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, silicone oil, and silicone masterbatch;

[0015] The flame retardant synergist includes one or more of antimony trioxide, zinc borate, barium metaborate, zinc oxide, molybdenum oxide, ammonium octamolybdate, ammonium polyphosphate, and zinc stannate;

[0016] The anti-copper agent includes one or more of bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, anti-copper agent PS802, anti-copper agent MD-697, and anti-copper agent HCA;

[0017] The halogen absorbent includes one or more of sodium, calcium and zinc stearates, silicates, hydrotalcites, metal oxides, lactates and benzoates;

[0018] The nano inorganic filler includes one or more of nano zinc oxide, nano titanium dioxide, nano calcium carbonate, white carbon black and nano clay.

[0019] Furthermore, the maleic anhydride grafted rubber elastomer copolymer is prepared by grafting and polymerizing a rubber elastomer with maleic anhydride and a cross-linking aid under the action of an initiator.

[0020] Further, the auxiliary cross-linking agent includes one or more of triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;

[0021] The initiator includes one or more of cumene peroxide, benzoyl peroxide, di-tert-butyl peroxide, di-tert-butyl hydroperoxide, and azobisisobutyronitrile;

[0022] A method for preparing a high temperature-resistant flame-retardant PP corrugated pipe comprises the following steps:

[0023] The flame retardant and the flame retardant synergist are mixed, and then a surface pre-dispersion treatment agent is added to perform dry surface pre-treatment, and spray drying is performed to obtain a flame retardant composite powder;

[0024] The flame retardant composite powder, nano inorganic filler, PP resin, first composite antioxidant, second composite antioxidant, anti-copper agent, halogen absorbent and lubricant are uniformly mixed, and screw granulated to obtain flame retardant masterbatch;

[0025] The flame retardant masterbatch, PP resin, rubber elastomer, maleic anhydride grafted rubber elastomer copolymer and color masterbatch are uniformly mixed, and extruded into a tube to obtain the high temperature resistant flame retardant PP corrugated tube.

[0026] Furthermore, the surface pretreatment agent includes one or two of calcium stearate, zinc stearate, magnesium stearate, ethylene bisstearamide, hydrotalcite, nano titanium dioxide, nano zinc oxide, sorbitan oleate, and polysorbate.

[0027] Furthermore, the method further comprises the following steps: preparing the flame retardant and the flame retardant synergist into powder, and sieving to control the powder particle size D90 to be 0.1 μm to 3.0 μm.

[0028] Furthermore, the preparation method of the maleic anhydride grafted rubber elastomer copolymer comprises the following process:

[0029] The rubber elastomer is added into a mixing chamber and stirred, and then a cross-linking agent and an initiator are added for mixing, and the product is dissolved into an organic solvent. After being fully dissolved at a constant temperature, a precipitant is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted rubber elastomer copolymer is obtained.

[0030] Furthermore, the organic solvent includes one or more of xylene, toluene, ethyl acetate, isopropanol, and butyl ester; the precipitant includes one or more of anhydrous ethanol, n-propanol, n-butanol, acetone, and n-hexane.

[0031] Beneficial effects of the present invention:

[0032] The invention provides a high temperature resistant flame retardant PP corrugated pipe, which uses polypropylene as the base material and is combined with a rubber elastomer to effectively improve the toughness and impact resistance of the material, and adds an appropriate amount of flame retardant to achieve UL The flame retardant requirements of 94-V0 level are met, while avoiding the embrittlement and uneven dispersion problems caused by excessive flame retardants; the introduction of maleic anhydride grafted rubber elastomer copolymers enhances the interfacial compatibility and inhibits the degradation caused by the flame retardant through the interaction of its polar functional groups with the base resin and flame retardants; in addition, these grafts can also react chemically with the acidic bromine free radicals generated by the high-temperature decomposition of brominated flame retardants to generate stable compounds, which significantly reduces the damage of acidic bromine free radicals to the material molecular chain, thereby ensuring the long-term stability of the material at high temperatures; the synergistic effect of the first composite antioxidant and the second composite antioxidant is the key to improving the high-temperature aging performance. The main antioxidant captures free radicals, and the auxiliary antioxidant decomposes peroxides to prevent oxidative degradation from different stages of the chemical chain reaction; this dual antioxidant mechanism enables the material to maintain good mechanical properties and appearance quality under high temperature and long-term use; the addition of lubricants optimizes the processing performance of the material and forms a micro-protective layer in the finished product, further reducing the surface damage caused by high-temperature aging. The PP corrugated pipe provided by the present invention not only significantly improves the flame retardant performance, but also achieves an ideal balance in terms of toughness, high temperature aging resistance and surface quality, successfully overcoming the problem in the prior art that it is difficult to achieve both flame retardancy and durability. DETAILED DESCRIPTION

[0033] The following is a further detailed description of a high temperature resistant and flame retardant PP corrugated pipe and a preparation method thereof described in the present invention in conjunction with the examples. For the sake of simplicity of description, this document cannot enumerate all alternative technical features and implementation schemes contained in the present invention. Therefore, those skilled in the art should know that any technical features and implementation schemes in this embodiment do not limit the scope of protection of the present invention, which includes any alternative technical features and implementation schemes adopted by all those skilled in the art without creative labor. Specifically, the implementation schemes obtained by replacing any technical feature in the present invention or combining any two or more technical features provided by the present invention should be within the scope of protection of the present invention.

[0034] The present embodiment provides a high temperature-resistant and flame-retardant PP corrugated pipe. The raw materials, measured in parts by weight, include: 40-60 parts of PP resin, 3-10 parts of rubber elastomer, 5-10 parts of maleic anhydride grafted rubber elastomer copolymer, 0.6-0.8 parts of maleic anhydride, 18-22 parts of flame retardant, 0.3-1 parts of first composite antioxidant, 0.5-1 parts of second composite antioxidant and 0.5-1.2 parts of lubricant.

[0035] In some embodiments, the raw materials, by weight, further include 6 to 12 parts of flame retardant synergist, 0.5 to 3 parts of copper resistant agent, 0.3 to 1 part of halogen absorber, 0.2 to 0.5 parts of nano inorganic filler and 1 to 1.5 parts of masterbatch.

[0036] In some embodiments, the PP resin includes one or two of homopolymer PP and copolymer PP; the copolymer PP brand includes one or more of K8303, K7002, TF1007, K8003, F5005A, and B4902;

[0037] The rubber elastomer includes one or more of EPDM rubber, polyolefin elastomer, EPDM rubber, butadiene rubber, natural rubber, and styrene-butadiene-styrene copolymer;

[0038] The flame retardant includes one or more of tris(tribromoneopentyl)phosphate, tris(2,3-dibromopropyl)isocyanurate, brominated epoxy resin, decabromodiphenylethane, octabromoether, tetrabromobisphenol A, hexabromocyclododecane, and brominated polystyrene;

[0039] The first composite antioxidant includes a first main antioxidant and a first auxiliary antioxidant, wherein the first main antioxidant includes one or more of antioxidant 1010, antioxidant CA, antioxidant 2246, and antioxidant 1024; the first auxiliary antioxidant includes one or more of antioxidant DLTDP, antioxidant DSTDP, antioxidant 412S, and antioxidant SE-10;

[0040] The second composite antioxidant includes a second main antioxidant and a second auxiliary antioxidant, wherein the second main antioxidant includes one or more of antioxidant 1076, antioxidant 264, antioxidant 245, antioxidant 3114, and antioxidant 1098; the second auxiliary antioxidant includes one or more of antioxidant 168, antioxidant 626, and antioxidant P-EPQ;

[0041] The lubricant includes one or more of paraffin wax, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, silicone oil, and silicone masterbatch;

[0042] The flame retardant synergist includes one or more of antimony trioxide, zinc borate, barium metaborate, zinc oxide, molybdenum oxide, ammonium octamolybdate, ammonium polyphosphate, and zinc stannate;

[0043] The anti-copper agent includes one or more of bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, anti-copper agent PS802, anti-copper agent MD-697, and anti-copper agent HCA;

[0044] The halogen absorbent includes one or more of sodium, calcium and zinc stearates, silicates, hydrotalcites, metal oxides, lactates and benzoates;

[0045] The nano inorganic filler includes one or more of nano zinc oxide, nano titanium dioxide, nano calcium carbonate, white carbon black and nano clay.

[0046] In some embodiments, the maleic anhydride grafted rubber elastomer copolymer is prepared by grafting and polymerizing a rubber elastomer with maleic anhydride and a cross-linking aid under the action of an initiator.

[0047] In some embodiments, the auxiliary cross-linking agent includes one or more of triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;

[0048] The initiator includes one or more of cumene peroxide, benzoyl peroxide, di-tert-butyl peroxide, di-tert-butyl hydroperoxide, and azobisisobutyronitrile;

[0049] This embodiment provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0050] The flame retardant and the flame retardant synergist are mixed, and then a surface pre-dispersion treatment agent is added to perform dry surface pre-treatment, and spray drying is performed to obtain a flame retardant composite powder;

[0051] The flame retardant composite powder, nano inorganic filler, PP resin, the first composite antioxidant, the second composite antioxidant, the anti-copper agent, the halogen absorbent and the lubricant are uniformly mixed, and the mixture is granulated by a screw to obtain a flame retardant masterbatch;

[0052] The flame retardant masterbatch, PP resin, rubber elastomer, maleic anhydride grafted rubber elastomer copolymer and color masterbatch are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0053] In the above embodiment, first, the flame retardant and the flame retardant synergist are mixed and a surface pre-dispersion treatment agent is added for dry surface treatment, and the spray drying technology is used to achieve uniform particle size and improved dispersibility of the flame retardant composite powder. This step not only avoids the agglomeration of the flame retardant in the matrix, but also enhances the compatibility of the flame retardant with the matrix material, laying the foundation for achieving efficient flame retardant performance.

[0054] Subsequently, the flame retardant masterbatch was prepared by mixing the composite flame retardant powder with nano inorganic fillers, antioxidants, anti-copper agents and other functional additives and screw granulating. During the screw granulation process, the components were evenly dispersed under the action of shear force and high temperature, and a stable composite structure was formed. The addition of nano inorganic fillers further improved the thermal stability of the composite masterbatch. The antioxidant effectively delayed the high temperature aging process by capturing free radicals and decomposing peroxides, while the synergistic effect of the anti-copper agent and the halogen absorber significantly reduced the damage to the material properties caused by copper ion catalytic degradation and halogen residues.

[0055] Finally, the flame retardant masterbatch was mixed with PP resin, rubber elastomer, maleic anhydride grafted rubber elastomer copolymer and color masterbatch and extruded into tubes, which fully utilized the polar functional groups of the grafted copolymer and the flexible molecular chain structure of the rubber elastomer, improved the toughness and impact resistance of the material, and stabilized the acidic free radicals produced by the high-temperature decomposition of the brominated flame retardant to prevent further precipitation and degradation of the base material. During the molding process, the components in the masterbatch were evenly distributed in the base material, so that the final corrugated tube had excellent flame retardancy, high temperature resistance and anti-aging ability.

[0056] In some embodiments, the surface pretreatment agent includes one or two of calcium stearate, zinc stearate, magnesium stearate, ethylene bisstearamide, hydrotalcite, nano titanium dioxide, nano zinc oxide, sorbitan oleate, and polysorbate.

[0057] Stearates (such as calcium stearate, zinc stearate, and magnesium stearate) form a hydrophobic protective layer on the particle surface through their long-chain fatty acid molecular structure, reducing the van der Waals force between particles, thereby effectively preventing the agglomeration of flame retardant particles. At the same time, these stearates can also provide lubrication under high temperature conditions, further improving processing performance and reducing energy consumption during screw extrusion.

[0058] As an efficient dispersant and lubricant, ethylene bisstearamide (EBS) not only improves the uniformity of the dispersion of flame retardant particles in the matrix, but also enhances the interfacial compatibility through the physical interaction between its bisamide group and the polymer matrix. Nano-inorganic substances such as nano-titanium dioxide and nano-zinc oxide can form a stable dispersion network around flame retardant particles through their high specific surface area and surface activity, while providing additional thermal stability and optical stability.

[0059] Surfactants such as sorbitan oleate and polysorbate further utilize their surface wetting properties to reduce the interfacial tension between the particles and the matrix, enhancing the dispersion effect of the flame retardant particles. In addition, these surfactants can effectively control the particle size distribution during the spray drying process to ensure the uniformity of the particle size, thereby achieving the best processing rheological properties during the screw granulation and final extrusion tube molding process.

[0060] The synergistic effect of these surface pretreatment agents not only effectively solves the problems of agglomeration and uneven dispersion of flame retardant and synergist particles, but also further optimizes the material properties during high-temperature processing, ensuring that the final PP corrugated pipe achieves an ideal balance between flame retardancy, mechanical properties and long-term stability.

[0061] In some embodiments, the following process is also included: the flame retardant and the flame retardant synergist are made into powder, and the powder particle size D90 is controlled by screening to be 0.1 μm to 3.0 μm.

[0062] By controlling the particle size of the powder in the submicron to low micron range, the specific surface area of ​​the flame retardant particles can be significantly increased. This higher specific surface area not only enhances the physical contact between the flame retardant and the polypropylene matrix, but also improves the activity of the chemical interface, thereby achieving more efficient flame retardant performance at a lower addition amount. In addition, the fine and uniform particle distribution can prevent the flame retardant from forming aggregation points in the matrix, fundamentally reducing the deterioration of mechanical properties and surface defects caused by particle agglomeration.

[0063] The uniformity of particle size is ensured through precise screening, avoiding uneven heating of large particles during high-temperature extrusion. This strict particle size control not only improves the dispersion uniformity of powder in masterbatch preparation and final product processing, but also reduces the wear of processing equipment and improves production efficiency.

[0064] For flame retardant synergists, smaller particle size and uniform distribution make their synergistic effect in flame retardants more significant, for example, by increasing the formation rate and stability of the char layer, further enhancing the heat shielding effect and anti-dripping performance of the flame retardant system.

[0065] In some embodiments, the method for preparing the maleic anhydride grafted rubber elastomer copolymer comprises the following process:

[0066] The rubber elastomer is added into a mixing chamber and stirred, and then a cross-linking agent and an initiator are added for mixing, and the product is dissolved into an organic solvent. After being fully dissolved at a constant temperature, a precipitant is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted rubber elastomer copolymer is obtained.

[0067] In some embodiments, the organic solvent includes one or more of xylene, toluene, ethyl acetate, isopropanol, and butyl ester; the precipitant includes one or more of anhydrous ethanol, n-propanol, n-butanol, acetone, and n-hexane.

[0068] In the above embodiment, first, the rubber elastomer is added to the mixing chamber and stirred, and the active sites of its molecular chain segments are opened by thermomechanical action. Under the synergistic effect of the co-crosslinking agent and the initiator, maleic anhydride can quickly form chemical bonds with the molecular chains of the rubber elastomer, thereby achieving an efficient grafting reaction. The high shear force and uniform heating during the mixing process ensure the sufficiency of the grafting reaction and the molecular structure stability of the product.

[0069] The grafted product is dissolved in an organic solvent (such as xylene, toluene, etc.). This process not only further releases the interchain entanglement of the rubber elastomer, but also provides a good reaction environment for subsequent purification. The selection of organic solvents is based on their solubility and volatility, ensuring that the grafted product remains chemically stable during the dissolution process, while facilitating subsequent precipitation and solvent recovery.

[0070] During the purification process, the grafted product is selectively precipitated from the solution by adding a precipitant (such as anhydrous ethanol, acetone, n-hexane, etc.). The role of the precipitant is to reduce the solubility of the grafted product and separate it from the unreacted products or by-products. Multiple dissolution-precipitation cycles further improve the purity of the grafted product and reduce the presence of residual reactants or impurities. In addition, the combination of different solvents and precipitants can be flexibly adjusted according to the characteristics of the grafted product to optimize the purification effect.

[0071] The successful introduction of polar maleic anhydride groups in the graft copolymer significantly enhances its compatibility with the polypropylene matrix, while improving the durability of the material through the stability of the chemical bonds. The use of co-crosslinking agents makes the grafting reaction more efficient, while multiple purification steps ensure the high purity of the product and avoid the adverse effects of impurities on the material properties. In addition, by carefully controlling the combination of organic solvents and precipitants, the molecular structure integrity and processing adaptability of the product can be maximized.

[0072] Example

[0073] Example 1

[0074] Example 1 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 40 kg of PP resin (homopolymer PP resin K7002), 3 kg of polyolefin elastomer POE, 5 kg of maleic anhydride grafted polyolefin elastomer copolymer, 18 kg of flame retardant decabromodiphenyl ethane, 0.3 kg of a first composite antioxidant, 0.5 kg of a second composite antioxidant and 0.5 kg of lubricant ethylene bisstearamide; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1010 to antioxidant DLTDP is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1076 to antioxidant 168 is 1:1.

[0075] Embodiment 1 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0076] The flame retardant decabromodiphenylethane is added to the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain decabromodiphenylethane powder;

[0077] The decabromodiphenylethane powder, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant ethylene bis stearamide are uniformly mixed, and the mixture is granulated by a screw to obtain a flame retardant masterbatch;

[0078] The flame retardant masterbatch, PP resin, polyolefin elastomer POE and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0079] Embodiment 1 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0080] Add polyolefin elastomer POE into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator cumene peroxide for mixing, dissolve the product in xylene, add the precipitant anhydrous ethanol after fully dissolving at a constant temperature of 60°C, filter, and obtain the maleic anhydride grafted polyolefin elastomer copolymer after multiple dissolution and precipitation.

[0081] Example 2

[0082] Example 2 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 50 kg of PP resin (block copolymer PP resin K8003), 5 kg of EPDM rubber, 7.5 kg of maleic anhydride grafted EPDM rubber elastomeric copolymer, 20 kg of flame retardant tetrabromobisphenol A, 0.6 kg of a first composite antioxidant, 0.8 kg of a second composite antioxidant and 0.8 kg of lubricant calcium stearate; wherein the first composite antioxidant is a composite antioxidant with a mass ratio of 2:1 between antioxidant 1024 and antioxidant DSTDP; the second composite antioxidant is a composite antioxidant with a mass ratio of 2:1 between antioxidant 264 and antioxidant 626.

[0083] Embodiment 2 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0084] The flame retardant tetrabromobisphenol A is added to the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain tetrabromobisphenol A powder;

[0085] Tetrabromobisphenol A powder, PP resin, the first composite antioxidant, the second composite antioxidant, and lubricant calcium stearate are uniformly mixed, and screw granulated to obtain a flame retardant masterbatch;

[0086] The flame retardant masterbatch, PP resin, EPDM and maleic anhydride grafted EPDM elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0087] Embodiment 2 also provides a method for preparing a maleic anhydride grafted EPDM rubber elastomeric copolymer, comprising the following steps:

[0088] Add EPDM into a mixing chamber and stir, then add a cross-linking agent, triallyl isocyanurate, and an initiator, cumene peroxide, for mixing, dissolve the product in toluene, keep the temperature at 60°C until fully dissolved, add anhydrous ethanol as a precipitant, filter, and obtain a maleic anhydride grafted EPDM elastomer copolymer after multiple dissolutions and precipitations.

[0089] Example 3

[0090] Example 3 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 60kg of PP resin (copolymer PP resin F5005A), 10kg of butadiene rubber BR, 10kg of maleic anhydride grafted butadiene rubber elastomer copolymer, 22kg of flame retardant brominated epoxy resin BEO, 1.0kg of a first composite antioxidant, 1.0kg of a second composite antioxidant and 1.2kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 2246 and antioxidant SE-10 is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1098 and antioxidant P-EPQ is 1:1.

[0091] Embodiment 3 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0092] The flame retardant brominated epoxy resin BEO is added with the surface pre-dispersed treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain brominated epoxy resin BEO powder;

[0093] The brominated epoxy resin BEO powder, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant polyethylene wax are uniformly mixed, and the mixture is granulated by a screw to obtain a flame retardant masterbatch;

[0094] The flame retardant masterbatch, PP resin, butadiene rubber (BR) and maleic anhydride grafted butadiene rubber elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0095] Embodiment 3 also provides a method for preparing a maleic anhydride grafted butadiene rubber elastomer copolymer, comprising the following steps:

[0096] Add butyl rubber BR into a mixing chamber and stir, then add a cross-linking agent triallyl isocyanurate and an initiator benzoyl peroxide for mixing, dissolve the product in xylene, add a precipitant n-propanol after fully dissolving at a constant temperature of 70°C, filter, and obtain a maleic anhydride grafted butyl rubber elastomer copolymer after multiple dissolution and precipitation.

[0097] Example 4

[0098] Example 4 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 45 kg of PP resin (homopolymer PP resin K7002), 6 kg of styrene-butadiene-styrene copolymer SBS, 6 kg of maleic anhydride grafted styrene-butadiene-styrene copolymer, 18 kg of flame retardant tri(tribromoneopentyl) phosphate, 0.4 kg of a first composite antioxidant, 0.6 kg of a second composite antioxidant and 0.6 kg of lubricant zinc stearate; wherein the first composite antioxidant is a composite antioxidant of antioxidant CA and antioxidant DLTDP in a mass ratio of 2:1; the second composite antioxidant is a composite antioxidant of antioxidant 264 and antioxidant 626 in a mass ratio of 2:1.

[0099] Embodiment 4 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0100] The flame retardant tris(tribromoneopentyl) phosphate is added to the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain tris(tribromoneopentyl) phosphate powder;

[0101] The tri(tribromoneopentyl)phosphate powder, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant zinc stearate are uniformly mixed, and the mixture is screw-granulated to obtain a flame retardant masterbatch;

[0102] The flame retardant masterbatch, PP resin, styrene-butadiene-styrene copolymer SBS and maleic anhydride grafted styrene-butadiene-styrene copolymer are uniformly mixed and extruded to form a tube, thereby preparing a high temperature resistant flame retardant PP corrugated tube.

[0103] Embodiment 4 also provides a method for preparing a maleic anhydride grafted styrene-butadiene-styrene copolymer, comprising the following steps:

[0104] Styrene-butadiene-styrene copolymer SBS is added into a mixing chamber and stirred, and then a cross-linking agent triallyl isocyanurate and an initiator cumene peroxide are added for mixing, and the product is dissolved in toluene. After being fully dissolved at a constant temperature of 60°C, a precipitant acetone is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted styrene-butadiene-styrene copolymer is obtained.

[0105] Example 5

[0106] Example 5 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 55 kg of PP resin (copolymer PP resin B4902), 4 kg of polyolefin elastomer POE, 7 kg of maleic anhydride grafted polyolefin elastomer copolymer, 21 kg of flame retardant decabromodiphenyl ethane DBDPE, 0.8 kg of a first composite antioxidant, 0.9 kg of a second composite antioxidant and 0.9 kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1010 to antioxidant DLTDP is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1076 to antioxidant 168 is 1:1.

[0107] Embodiment 5 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0108] The flame retardant decabromodiphenylethane (DBDPE) is added with the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain decabromodiphenylethane (DBDPE) powder;

[0109] Decabromodiphenylethane DBDPE powder, PP resin, the first composite antioxidant, the second composite antioxidant, and lubricant polyethylene wax are uniformly mixed, and screw pelletized to obtain a flame retardant masterbatch;

[0110] The flame retardant masterbatch, PP resin, polyolefin elastomer POE and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0111] Embodiment 5 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0112] The polyolefin elastomer POE is added into a mixing chamber and stirred, and then the co-crosslinking agent triallyl isocyanurate and the initiator benzoyl peroxide are added for mixing, and the product is dissolved in xylene. After fully dissolved at a constant temperature of 60°C, anhydrous ethanol as a precipitant is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted polyolefin elastomer copolymer is obtained.

[0113] Example 6

[0114] Example 6 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 42 kg of PP resin (homopolymer PP resin K8303), 7 kg of polyolefin elastomer POE, 6 kg of maleic anhydride grafted polyolefin elastomer copolymer, 19 kg of flame retardant decabromodiphenyl ethane DBDPE, 0.5 kg of a first composite antioxidant, 0.7 kg of a second composite antioxidant and 0.5 kg of lubricant calcium stearate; wherein the first composite antioxidant is a composite antioxidant of antioxidant 2246 and antioxidant SE-10 in a mass ratio of 1:1; the second composite antioxidant is a composite antioxidant of antioxidant 1098 and antioxidant 168 in a mass ratio of 1:1.

[0115] Example 6 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0116] The flame retardant decabromodiphenylethane (DBDPE) is added with the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain decabromodiphenylethane (DBDPE) powder;

[0117] Decabromodiphenylethane DBDPE powder, PP resin, the first composite antioxidant, the second composite antioxidant, and lubricant calcium stearate are uniformly mixed, and screw granulated to obtain a flame retardant masterbatch;

[0118] The flame retardant masterbatch, PP resin, polyolefin elastomer POE and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0119] Embodiment 6 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0120] Add polyolefin elastomer POE into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator benzoyl peroxide for mixing, dissolve the product in toluene, add the precipitant anhydrous ethanol after fully dissolving at a constant temperature of 60°C, filter, and obtain the maleic anhydride grafted polyolefin elastomer copolymer after multiple dissolution and precipitation.

[0121] Example 7

[0122] Example 7 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 55kg of PP resin (copolymer PP resin F5005A), 4kg of butadiene rubber BR, 8kg of maleic anhydride grafted butadiene rubber elastomer copolymer, 1kg of flame retardant brominated epoxy resin BEO, 0.7kg of a first composite antioxidant, 0.9kg of a second composite antioxidant and 1.0kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant of antioxidant 1010 and antioxidant DLTDP in a mass ratio of 1:1; the second composite antioxidant is a composite antioxidant of antioxidant 3114 and antioxidant 168 in a mass ratio of 1:1.

[0123] Example 7 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0124] The flame retardant brominated epoxy resin BEO is added with the surface pre-dispersed treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain brominated epoxy resin BEO powder;

[0125] The brominated epoxy resin BEO powder, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant polyethylene wax are uniformly mixed, and the mixture is granulated by a screw to obtain a flame retardant masterbatch;

[0126] The flame retardant masterbatch, PP resin, butadiene rubber (BR) and maleic anhydride grafted butadiene rubber elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0127] Embodiment 7 also provides a method for preparing a maleic anhydride grafted butadiene rubber elastomer copolymer, comprising the following steps:

[0128] Add butyl rubber BR into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator cumene peroxide for mixing, dissolve the product in xylene, add the precipitant n-propanol after fully dissolving at 70°C, filter, and obtain the maleic anhydride grafted butyl rubber elastomer copolymer after multiple dissolution and precipitation.

[0129] Example 8

[0130] Example 8 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 50 kg of PP resin (homopolymer PP resin K7002), 5 kg of styrene-butadiene-styrene copolymer SBS, 8 kg of maleic anhydride grafted styrene-butadiene-styrene copolymer, 18 kg of flame retardant tri(tribromoneopentyl) phosphate, 0.6 kg of a first composite antioxidant, 0.8 kg of a second composite antioxidant and 0.7 kg of lubricant calcium stearate; wherein the first composite antioxidant is a composite antioxidant of antioxidant 2246 and antioxidant SE-10 in a mass ratio of 1:1; the second composite antioxidant is a composite antioxidant of antioxidant 1098 and antioxidant 168 in a mass ratio of 1:1.

[0131] Embodiment 8 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0132] The flame retardant tris(tribromoneopentyl) phosphate is added to the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain tris(tribromoneopentyl) phosphate powder;

[0133] The tri(tribromoneopentyl)phosphate powder, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant calcium stearate are uniformly mixed, and the mixture is granulated by a screw to obtain a flame retardant masterbatch;

[0134] The flame retardant masterbatch, PP resin, styrene-butadiene-styrene copolymer SBS and maleic anhydride grafted styrene-butadiene-styrene copolymer are uniformly mixed and extruded to form a tube, thereby preparing a high temperature resistant flame retardant PP corrugated tube.

[0135] Embodiment 8 also provides a method for preparing a maleic anhydride grafted styrene-butadiene-styrene copolymer, comprising the following steps:

[0136] Styrene-butadiene-styrene copolymer SBS is added into a mixing chamber and stirred, and then a cross-linking agent triallyl isocyanurate and an initiator cumene peroxide are added for mixing, and the product is dissolved in toluene. After being fully dissolved at a constant temperature of 60°C, a precipitant acetone is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted styrene-butadiene-styrene copolymer is obtained.

[0137] Example 9

[0138] Example 9 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 45 kg of PP resin (copolymer PP resin B4902), 8 kg of polyolefin elastomer POE, 9 kg of maleic anhydride grafted polyolefin elastomer copolymer, 21 kg of flame retardant decabromodiphenylethane DBDPE, 0.5 kg of a first composite antioxidant, 0.7 kg of a second composite antioxidant and 0.8 kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant of antioxidant 1010 and antioxidant DLTDP in a mass ratio of 1:1; the second composite antioxidant is a composite antioxidant of antioxidant 264 and antioxidant 626 in a mass ratio of 2:1.

[0139] Example 9 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0140] The flame retardant decabromodiphenylethane (DBDPE) is added with the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain decabromodiphenylethane (DBDPE) powder;

[0141] Decabromodiphenylethane DBDPE powder, PP resin, the first composite antioxidant, the second composite antioxidant, and lubricant polyethylene wax are uniformly mixed, and screw pelletized to obtain a flame retardant masterbatch;

[0142] The flame retardant masterbatch, PP resin, polyolefin elastomer POE and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0143] Embodiment 9 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0144] Add polyolefin elastomer POE into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator cumene peroxide for mixing, dissolve the product in xylene, add the precipitant anhydrous ethanol after fully dissolving at a constant temperature of 60°C, filter, and obtain the maleic anhydride grafted polyolefin elastomer copolymer after multiple dissolution and precipitation.

[0145] Example 10

[0146] Example 10 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 48 kg of PP resin (homopolymer PP resin K8303), 5 kg of polyolefin elastomer POE, 7 kg of maleic anhydride grafted polyolefin elastomer copolymer, 21 kg of flame retardant tetrabromobisphenol A, 0.7 kg of a first composite antioxidant, 0.9 kg of a second composite antioxidant and 0.8 kg of lubricant calcium stearate; wherein the first composite antioxidant is a composite antioxidant of antioxidant 2246 and antioxidant SE-10 in a mass ratio of 1:1; the second composite antioxidant is a composite antioxidant of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1.

[0147] Embodiment 10 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0148] The flame retardant tetrabromobisphenol A is added to the surface pre-dispersion treatment agent calcium stearate for dry surface pre-treatment, and spray-dried to obtain tetrabromobisphenol A powder;

[0149] Tetrabromobisphenol A powder, PP resin, the first composite antioxidant, the second composite antioxidant, and lubricant calcium stearate are uniformly mixed, and screw granulated to obtain a flame retardant masterbatch;

[0150] The flame retardant masterbatch, PP resin, polyolefin elastomer POE and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to form a tube, so as to obtain a high temperature resistant flame retardant PP corrugated tube.

[0151] Embodiment 10 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0152] Add polyolefin elastomer POE into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator cumene peroxide for mixing, dissolve the product in toluene, add the precipitant anhydrous ethanol after fully dissolving at a constant temperature of 60°C, filter, and obtain the maleic anhydride grafted polyolefin elastomer copolymer after multiple dissolution and precipitation.

[0153] Embodiment 11

[0154] Example 11 provides a high temperature-resistant flame-retardant PP corrugated pipe, the raw materials including: 50kg of PP resin (copolymer PP resin K7002), 5kg of EPDM rubber, 7kg of maleic anhydride grafted EPDM rubber elastomer copolymer, 20kg of flame retardant decabromodiphenylethane DBDPE, 6kg of flame retardant synergist antimony trioxide, 0.5kg of anti-copper agent bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, 0.3kg of halogen absorber sodium stearate, 0.2kg of nano titanium dioxide, 1kg of masterbatch, 0.6kg of a first composite antioxidant, 0.8kg of a second composite antioxidant and 0.9kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1010 to antioxidant DLTDP is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1076 to antioxidant 168 is 1:1.

[0155] Embodiment 11 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0156] The flame retardant decabromodiphenylethane DBDPE and the flame retardant synergist antimony trioxide are subjected to air flow grinding to control the particle size D90 < 3 μm, and the surface pre-dispersion treatment agent ethylene bis stearamide is added for dry surface pre-treatment, and spray drying is performed to obtain a flame retardant composite powder;

[0157] The flame retardant composite powder, the copper-damaging agent bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, the halogen absorbent sodium stearate, nano titanium dioxide, PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant polyethylene wax are mixed evenly, and the mixture is screw-granulated to obtain a flame retardant masterbatch;

[0158] The flame retardant masterbatch, PP resin, EPDM rubber, color masterbatch and maleic anhydride grafted EPDM rubber elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0159] Embodiment 11 also provides a method for preparing a maleic anhydride grafted EPDM rubber elastomeric copolymer, comprising the following steps:

[0160] Add EPDM into a mixing chamber and stir, then add a cross-linking agent, triallyl isocyanurate, and an initiator, cumene peroxide, for mixing, dissolve the product in toluene, keep the temperature at 60°C until fully dissolved, add anhydrous ethanol as a precipitant, filter, and obtain a maleic anhydride grafted EPDM elastomer copolymer after multiple dissolutions and precipitations.

[0161] Example 12

[0162] Example 12 provides a high temperature-resistant and flame-retardant PP corrugated pipe, the raw materials including: 60kg of PP resin (homopolymer PP resin K8303), 7kg of polyolefin elastomer POE, 9kg of maleic anhydride grafted polyolefin elastomer copolymer, 21kg of flame retardant tetrabromobisphenol A, 12kg of flame retardant synergist zinc oxide, 3kg of anti-copper agent PS802, 1kg of halogen absorber hydrotalcite, 0.5kg of nano calcium carbonate, 1.5kg of masterbatch, 0.8kg of a first composite antioxidant, 1.0kg of a second composite antioxidant and 0.9kg of lubricant calcium stearate; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 2246 to antioxidant SE-10 is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 3114 to antioxidant 168 is 1:1.

[0163] Embodiment 12 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0164] The flame retardant tetrabromobisphenol A and the flame retardant synergist zinc oxide are subjected to air flow grinding to control the particle size D90 < 2 μm, and the surface pre-dispersion treatment agent ethylene bisstearamide is added for dry surface pre-treatment, and spray drying is performed to obtain a flame retardant composite powder;

[0165] The flame retardant composite powder, the copper retardant PS802, the halogen absorber hydrotalcite, the nano calcium carbonate, the PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant calcium stearate are mixed evenly, and the mixture is screw-granulated to obtain the flame retardant masterbatch;

[0166] The flame retardant masterbatch, PP resin, polyolefin elastomer POE, color masterbatch and maleic anhydride grafted polyolefin elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0167] Embodiment 12 also provides a method for preparing a maleic anhydride grafted polyolefin elastomer copolymer, comprising the following steps:

[0168] Add polyolefin elastomer POE into a mixing chamber and stir, then add the cross-linking agent triallyl isocyanurate and the initiator cumene peroxide for mixing, dissolve the product in toluene, add the precipitant anhydrous ethanol after fully dissolving at a constant temperature of 60°C, filter, and obtain the maleic anhydride grafted polyolefin elastomer copolymer after multiple dissolution and precipitation.

[0169] Embodiment 13

[0170] Example 13 provides a high temperature-resistant flame-retardant PP corrugated pipe, the raw materials including: 55kg of PP resin (copolymer PP resin F5005A), 6kg of EPDM rubber, 8kg of maleic anhydride grafted EPDM rubber elastomer copolymer, 21kg of flame retardant brominated epoxy resin BEO, 9kg of flame retardant synergist molybdenum oxide, 2kg of anti-copper agent MD-697, 0.6kg of halogen absorber sodium benzoate, 0.4kg of nano zinc oxide, 1.2kg of masterbatch, 0.7kg of a first composite antioxidant, 1.0kg of a second composite antioxidant and 1.0kg of lubricant polyethylene wax; wherein the first composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1010 to antioxidant DLTDP is 1:1; the second composite antioxidant is a composite antioxidant in which the mass ratio of antioxidant 1076 to antioxidant 168 is 1:1.

[0171] Example 13 also provides a method for preparing a high temperature resistant flame retardant PP corrugated pipe, comprising the following steps:

[0172] The flame retardant brominated epoxy resin BEO and the flame retardant synergist molybdenum oxide are subjected to air flow grinding to control the particle size D90 < 1 μm, and the surface pre-dispersion treatment agent sorbitan oleate is added for dry surface pretreatment, and spray drying is performed to obtain a flame retardant composite powder;

[0173] The flame retardant composite powder, the copper resistant agent MD-697, the halogen absorber sodium benzoate, the nano zinc oxide, the PP resin, the first composite antioxidant, the second composite antioxidant, and the lubricant polyethylene wax are mixed evenly, and the mixture is screw-granulated to obtain the flame retardant masterbatch;

[0174] The flame retardant masterbatch, PP resin, EPDM rubber, color masterbatch and maleic anhydride grafted EPDM rubber elastomer copolymer are uniformly mixed and extruded to obtain a high temperature resistant flame retardant PP corrugated pipe.

[0175] Embodiment 13 also provides a method for preparing a maleic anhydride grafted EPDM rubber elastomeric copolymer, comprising the following steps:

[0176] Add EPDM into a mixing chamber and stir, then add a cross-linking agent, triallyl isocyanurate, and an initiator, benzoyl peroxide, for mixing, dissolve the product in xylene, add a precipitant, n-propanol, at 65°C, and filter, and obtain a maleic anhydride grafted EPDM elastomer copolymer after multiple dissolutions and precipitations.

[0177] Comparative Example

[0178] Comparative Example 1

[0179] Comparative Example 1 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that an equal amount of EPDM is replaced by a maleic anhydride grafted EPDM elastomeric copolymer.

[0180] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 1 is the same as that in Example 13.

[0181] Comparative Example 2

[0182] Comparative Example 2 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that an equal amount of maleic anhydride grafted EPDM rubber elastomeric copolymer is replaced by EPDM rubber.

[0183] Comparative Example 3

[0184] Comparative Example 3 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that maleic anhydride grafted EPDM rubber elastomeric copolymer and EPDM rubber EPDM are replaced by PP resin in equal amounts.

[0185] Comparative Example 4

[0186] Comparative Example 4 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that the flame retardant brominated epoxy resin BEO is replaced by an equal amount of flame retardant synergist molybdenum oxide.

[0187] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 4 is the same as that in Example 13.

[0188] Comparative Example 5

[0189] Comparative Example 5 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that the flame retardant synergist molybdenum oxide is replaced by an equal amount of the flame retardant brominated epoxy resin BEO.

[0190] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 5 is the same as that in Example 13.

[0191] Comparative Example 6

[0192] Comparative Example 6 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that the first composite antioxidant is replaced by an equal amount of the second composite antioxidant.

[0193] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 6 is the same as that in Example 13.

[0194] Comparative Example 7

[0195] Comparative Example 7 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that the second composite antioxidant is replaced by the first composite antioxidant in an equal amount.

[0196] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 7 is the same as that in Example 13.

[0197] Comparative Example 8

[0198] Comparative Example 8 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that the first composite antioxidant and the second composite antioxidant are replaced with PP resin in equal amounts.

[0199] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 8 is the same as that in Example 13.

[0200] Comparative Example 9

[0201] Comparative Example 9 provides a PP corrugated pipe and a preparation method thereof, which differs from Example 13 in that 9 equal amounts of maleic anhydride are replaced by PP resin.

[0202] The preparation method of the maleic anhydride grafted EPDM rubber elastomer copolymer provided in Comparative Example 9 is the same as that in Example 13.

[0203] Performance Testing

[0204] 1. Flame retardant performance test

[0205] The PP corrugated pipes provided in Examples 1-13 and Comparative Examples 1-9 were subjected to the following flame retardant performance tests, as follows:

[0206] 1. Limiting Oxygen Index (LOI)

[0207] Test Method

[0208] The oxygen index test is conducted according to ASTM D2863. The test uses a mixed gas of oxygen and nitrogen to adjust the oxygen concentration to determine the minimum oxygen content at which the material can maintain stable combustion. The experimental steps are as follows:

[0209] Prepare standard size specimens (length 70 mm, width 6.5 mm, thickness 3 mm);

[0210] Fix the sample vertically in the combustion chamber inside the LOI instrument;

[0211] Ignite the sample from the bottom, gradually adjust the oxygen concentration, and observe whether the sample can maintain stable combustion;

[0212] Record the minimum oxygen volume fraction required for combustion.

[0213] 2. UL-94 vertical burning rating

[0214] Test Method

[0215] The UL-94 test is based on the UL 94 standard and evaluates the self-extinguishing ability and dripping of materials after combustion. It is divided into horizontal combustion (HB) and vertical combustion (V-0, V-1, V-2) levels, with V-0 being the highest flame retardant level.

[0216] Test steps:

[0217] Prepare the specimen (125 mm × 13 mm × 3 mm);

[0218] Fix the sample vertically and ignite the bottom of the sample for 10 seconds;

[0219] Record the time when the flame goes out and observe whether the molten droplets ignite the cotton at the bottom;

[0220] Repeat the burning twice and determine the grade according to the standard.

[0221] 3. Heat Release Rate (HRR)

[0222] Test Method

[0223] HRR is tested by Cone Calorimeter according to ISO 5660-1 standard: The experimental steps are as follows:

[0224] Prepare the specimen (100 mm × 100 mm × 3 mm);

[0225] In a cone calorimeter at 35 kW / m 2 Ignite the sample under thermal radiation conditions;

[0226] The peak amount of heat released per unit time during the combustion of the test material.

[0227] 4. Total Heat Release (THR)

[0228] Test Method

[0229] THR and HRR tests are carried out simultaneously, indicating the total heat released by the sample during combustion, which is obtained by integrating the heat release rate curve.

[0230] 5. Smoke Density Rating (SDR)

[0231] Test Method

[0232] The smoke density test is based on the ASTM E662 standard to determine the smoke density generated when the material burns. The specific steps are as follows:

[0233] Prepare the specimen (75 mm × 75 mm × 3 mm);

[0234] The changes in smoke transmittance were recorded by an optical measuring device in a closed combustion box;

[0235] Calculate the maximum smoke density (Ds value).

[0236] 6. Thermal decomposition behavior

[0237] Test Method

[0238] The thermal stability and thermal decomposition behavior of the material were tested by thermogravimetric analyzer (TGA) according to ISO 11358 standard: The specific steps are as follows:

[0239] Under nitrogen protection, the heating rate was 10℃ / min, and the test temperature range was 30℃~800℃;

[0240] Record the initial decomposition temperature Maximum decomposition rate temperature (Tmax) and carbon residue rate.

[0241] The flame retardant performance test results of the PP corrugated pipes provided in Examples 1-13 and Comparative Examples 1-9 are shown in Table 1 below.

[0242] Table 1 Flame retardant properties of PP corrugated pipes provided by Examples 1-13 and Comparative Examples 1-9

[0243]

[0244]

[0245] As can be seen from Table 1, the data in Table 1 fully reflect the differences in flame retardancy, heat release characteristics, smoke density and thermal decomposition behavior between different embodiments and comparative examples. These data reflect the significant effects of material formulation and process optimization on the performance of PP corrugated pipes. From the perspective of oxygen index (LOI), the oxygen index of Examples 11-13 is significantly higher than that of other embodiments, reaching 31.2%, 32.1% and 32.5% respectively, indicating that these embodiments effectively improve the flame retardancy of the material through the synergistic effect of high-efficiency flame retardants and synergists, far exceeding the oxygen index of the comparative example (about 17.0%-19.0%). In particular, compared with Comparative Example 1, the oxygen index of Example 13 has increased by nearly 15 percentage points, which shows the effectiveness of the synergistic flame retardant system such as brominated epoxy resin and molybdenum oxide selected in the formula, and the material can quickly form a flame retardant protective layer during the combustion process to reduce the combustion rate.

[0246] In terms of flame extinguishing time, the flame extinguishing time of Examples 11-13 was shortened to 3.8-4.2 seconds, showing extremely strong self-extinguishing performance, while the comparative samples were generally between 18-20 seconds, indicating that the samples without the addition of the high-efficiency flame retardant system could not effectively inhibit the spread of combustion, and the burning time was significantly prolonged. In addition, the heat release rate (HRR) and total heat release (THR) further confirmed this difference. The HRR of Examples 11-13 was significantly reduced to 14.9-16.5kW / m 2 , THR drops to 30-32.5MJ / m 2 , indicating that the heat released by the material during combustion is significantly reduced, which helps to delay the spread of fire and reduce the risk of fire. The HRR value of the comparative example is as high as 30-35kW / m 2 ,THR exceeds 60MJ / m 2 , which indicates that the unoptimized formula is difficult to suppress the heat release generated during high-temperature pyrolysis, resulting in poor performance of the material in combustion.

[0247] Smoke density (Ds) is an important indicator for evaluating smoke generation during combustion. The Ds values ​​of Examples 11-13 are 5-7, which are much lower than 28-37 of the comparative examples. This shows that the optimized flame retardant formula can effectively reduce the high-temperature decomposition of organic matter and reduce the amount of smoke generated during combustion, which is of great significance for improving safety in practical application scenarios. In terms of thermal decomposition behavior, the initial decomposition temperature and maximum decomposition rate temperature of Examples 11-13 are increased to 295-305°C and 420-440°C, respectively, and the residual carbon rate is significantly increased to 9%-12%, which shows that the flame retardant system used not only enhances the thermal stability of the material, but also helps to form higher carbon residues during combustion, further blocking the transfer of heat and oxygen.

[0248] 2. High and low temperature resistance test

[0249] Test method: high and low temperature cycle test

[0250] Test conditions:

[0251] Place the PP corrugated pipe sample in a high and low temperature cycle test box, set the temperature range to -40℃ to 80℃, the cycle period is 2 hours (1 hour at high temperature + 1 hour at low temperature), and test 20 cycles.

[0252] After each cycle, the sample was returned to room temperature and then subjected to bending test.

[0253] Test content:

[0254] The flexibility of the hose was tested and the breaking strength of the samples was recorded.

[0255] Test results: The test results of high and low temperature resistance of the PP corrugated pipes provided in Examples 1-13 and Comparative Examples 1-9 are shown in Table 2.

[0256] Table 2 High and low temperature resistance test ( to 20 cycles)

[0257]

[0258]

[0259] As can be seen from Table 2, the data in Table 2 show the high and low temperature resistance of different embodiments and comparative examples under temperature cycles from -40°C to 80°C (20 times), including the initial bending radius, fracture strength retention rate and crack conditions. These indicators intuitively reflect the mechanical stability and structural integrity of the material under extreme temperature changes. The data of Examples 11-13 are particularly outstanding. The initial bending radii are 25mm, 24mm, and 26mm, respectively. After the temperature cycle test, the fracture strength retention rate is as high as 98%-100%, and no cracks appear, indicating that these three groups of embodiments show excellent low temperature toughness and high temperature stability under temperature shock. This performance improvement is due to the synergistic effect of the rubber elastomer, maleic anhydride graft copolymer and antioxidant in the formula, which effectively alleviates the internal stress of the material caused by temperature changes and improves the flexibility and fatigue resistance of the material.

[0260] In contrast, Examples 1-10 also performed relatively well, with the initial bending radius maintained at 18-23 mm, the fracture strength retention rate generally between **92%-97%**, and the cracks were only slight or no cracks, proving that these Examples also have good temperature cycle resistance. However, compared with Examples 11-13, these Examples are slightly inferior in strength retention and initial bending radius, indicating that there are still differences in the proportion of rubber elastomers, lubricants, and the degree of optimization of the antioxidant system in the formula.

[0261] In sharp contrast, the data of Comparative Examples 1-9 show that the initial bending radius of these samples is significantly smaller, generally between 12-16 mm, indicating that the flexibility of the material in the initial state is poor. After 20 temperature cycles, the fracture strength retention rate dropped significantly, and some samples were even lower than 60%, especially Comparative Examples 7-9, where the cracks were serious, and obvious cracks or structural damage appeared on the surface. This shows that the comparative samples did not introduce rubber elastomers and appropriate maleic anhydride grafted copolymers, and the impact resistance and structural stability of the materials under extreme temperature changes were insufficient, and the internal stress caused by thermal expansion and contraction could not be effectively alleviated, resulting in a sharp deterioration of performance.

[0262] 3. Anti-copper damage performance test

[0263] Test method for copper resistance

[0264] Wrap the surface of the copper wire braided mesh tube with 10 turns of PVC tape, insert it into the corrugated tube, seal the two ends of the corrugated tube with silicone, and then place it in a 120℃ environment for 3000 hours. Record the time when the corrugated tube sample is not brittle or powdered. The corrugated tube sample that is not brittle or powdered for more than 3000 hours is qualified.

[0265] The PP corrugated pipes provided in Examples 1-13 and Comparative Examples 1-9 were subjected to the above-mentioned copper damage resistance test, and the results are shown in Table 3 below.

[0266] Table 3 Anti-copper damage performance test

[0267]

[0268] As can be seen from Table 3, from the data, the pulverization time of Examples 11-13 is more than 3000 hours, showing extremely excellent anti-copper damage performance. This performance is attributed to the introduction of anti-copper damage agents (such as bis (3,5-di-tert-butyl-4-hydroxy-phenylpropionyl) hydrazine, PS802, MD-697, etc.) in the formula, as well as the synergistic effect of halogen absorbers and nano-inorganic fillers. These components effectively neutralize or capture copper ions in a copper-damaged environment, inhibiting their oxidative degradation of polypropylene molecular chains, thereby delaying the occurrence of pulverization. In addition, the optimized composite antioxidant system further enhances the antioxidant stability of the material, prolongs the pulverization time, and enables the material to maintain good stability and structural integrity in a long-term service environment.

[0269] For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived from them are still within the scope of protection of the claims of the invention.

Claims

1. A high temperature resistant flame retardant PP corrugated pipe, characterized in that: The raw materials, measured in parts by weight, include: 40-60 parts of PP resin, 3-10 parts of rubber elastomer, 5-10 parts of maleic anhydride grafted rubber elastomer copolymer, 0.6-0.8 parts of maleic anhydride, 18-22 parts of flame retardant, 0.3-1 parts of first composite antioxidant, 0.5-1 parts of second composite antioxidant and 0.5-1.2 parts of lubricant.

2. According to claim 1, a high temperature resistant flame retardant PP corrugated pipe is characterized in that: The raw materials, calculated by weight, also include 6-12 parts of flame retardant synergist, 0.5-3 parts of copper resistant agent, 0.3-1 parts of halogen absorber, 0.2-0.5 parts of nano inorganic filler and 1-1.5 parts of masterbatch.

3. The high temperature resistant and flame retardant PP corrugated pipe according to claim 2, characterized in that: The PP resin includes one or two of homopolymer PP and copolymer PP; the copolymer PP brand includes one or more of K8303, K7002, TF1007, K8003, F5005A, and B4902; The rubber elastic body includes one or more of EPDM rubber, polyolefin elastomer, EPDM rubber, butadiene rubber, natural rubber, and styrene-butadiene-styrene copolymer; The flame retardant includes one or more of tris(tribromoneopentyl)phosphate, tris(2,3-dibromopropyl)isocyanurate, brominated epoxy resin, decabromodiphenylethane, octabromoether, tetrabromobisphenol A, hexabromocyclododecane, and brominated polystyrene; The first composite antioxidant includes a first main antioxidant and a first auxiliary antioxidant, wherein the first main antioxidant includes one or more of antioxidant 1010, antioxidant CA, antioxidant 2246, and antioxidant 1024; the first auxiliary antioxidant includes one or more of antioxidant DLTDP, antioxidant DSTDP, antioxidant 412S, and antioxidant SE-10; The second composite antioxidant includes a second main antioxidant and a second auxiliary antioxidant, wherein the second main antioxidant includes one or more of antioxidant 1076, antioxidant 264, antioxidant 245, antioxidant 3114, and antioxidant 1098; the second auxiliary antioxidant includes one or more of antioxidant 168, antioxidant 626, and antioxidant P-EPQ; The lubricant includes one or more of paraffin wax, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, silicone oil, and silicone masterbatch; The flame retardant synergist includes one or more of antimony trioxide, zinc borate, barium metaborate, zinc oxide, molybdenum oxide, ammonium octamolybdate, ammonium polyphosphate, and zinc stannate; The anti-copper agent includes one or more of bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, anti-copper agent PS802, anti-copper agent MD-697, and anti-copper agent HCA; The halogen absorbent includes one or more of sodium, calcium and zinc stearates, silicates, hydrotalcites, metal oxides, lactates and benzoates; The nano inorganic filler includes one or more of nano zinc oxide, nano titanium dioxide, nano calcium carbonate, white carbon black and nano clay.

4. The high temperature resistant and flame retardant PP corrugated pipe according to claim 3, characterized in that: The maleic anhydride grafted rubber elastic body copolymer is prepared by grafting and polymerizing the rubber elastic body with maleic anhydride and a cross-linking aid under the action of an initiator.

5. The high temperature resistant and flame retardant PP corrugated pipe according to claim 4, characterized in that: The auxiliary cross-linking agent includes one or more of triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate; The initiator includes one or more of cumene peroxide, benzoyl peroxide, di-tert-butyl peroxide, di-tert-butyl hydroperoxide, and azobisisobutyronitrile.

6. A method for preparing the high temperature resistant flame retardant PP corrugated pipe according to any one of claims 2 to 5, characterized in that: The process includes: The flame retardant and the flame retardant synergist are mixed, and then a surface pre-dispersion treatment agent is added to perform dry surface pre-treatment, and spray drying is performed to obtain a flame retardant composite powder; The flame retardant composite powder, nano inorganic filler, PP resin, first composite antioxidant, second composite antioxidant, anti-copper agent, halogen absorbent and lubricant are uniformly mixed, and screw granulated to obtain flame retardant masterbatch; The flame retardant masterbatch, PP resin, rubber elastomer, maleic anhydride grafted rubber elastomer copolymer and color masterbatch are uniformly mixed, and extruded into a tube to obtain the high temperature resistant flame retardant PP corrugated tube.

7. The method for preparing a high temperature resistant and flame retardant PP corrugated pipe according to claim 6, characterized in that: The surface pretreatment agent includes one or two of calcium stearate, zinc stearate, magnesium stearate, ethylene bis stearamide, hydrotalcite, nano titanium dioxide, nano zinc oxide, sorbitan oleate and polysorbate.

8. The method for preparing a high temperature resistant and flame retardant PP corrugated pipe according to claim 6, characterized in that: The method also includes the following steps: preparing the flame retardant and the flame retardant synergist into powder, and screening to control the powder particle size D90 to be 0.1 μm to 3.0 μm.

9. The method for preparing a high temperature resistant and flame retardant PP corrugated pipe according to claim 6, characterized in that: The preparation method of the maleic anhydride grafted rubber elastomer copolymer, The process includes: The rubber elastomer is added into a mixing chamber and stirred, and then a cross-linking agent and an initiator are added for mixing, and the product is dissolved into an organic solvent. After being fully dissolved at a constant temperature, a precipitant is added, and the product is filtered. After multiple dissolutions and precipitations, a maleic anhydride grafted rubber elastomer copolymer is obtained.

10. The method for preparing a high temperature resistant and flame retardant PP corrugated pipe according to claim 9, characterized in that: The organic solvent includes one or more of xylene, toluene, ethyl acetate, isopropanol, and butyl ester; the precipitant includes one or more of anhydrous ethanol, n-propanol, n-butanol, acetone, and n-hexane.